Combining Ranked Mean Value Forecasts. - Mostaghimi, Mehdi (1993)
Keywords: dept.eco; faculty_collection; sabbatical_report

Obstacles to trade liberalization and economic cooperation among west African states - Gebremariam, Yilma (Journal of International Development, 1993)
Does the formation of a customs union reduce and eventually eliminate tariffs among member countries to provide mechanisms or regional institutions for social, economic and political development? The literature examined suggests that, although many problems of trade liberalization continue to occur, greater benefits could be obtained by reducing tariffs on a non‐discriminatory basis, or by removing protection from domestic enterprises altogether, and by importing domestic requirements of the products of displaced industries from outside at world market prices. The literature also provides a valid case for protecting certain activities in ECOWAS — particularly trade and industrial enterprises — either for the purpose of increasing income or the rate of economic growth, or in order to achieve certain non‐economic objectives. The implications of economic integration in these terms can best be examined within a broader theoretical framework of developmental theory of trade liberalization. Copyright © 1993 John Wiley & Sons, Ltd
Keywords: Africa, (West); ECOWAS; customs union; dept.eco; developing country; economic cooperation; free trade area; international trade; regional cooperation; tariff reduction; trade liberalisation

The british population - patterns, trends, and processes - coleman,d, salt,j - Mills, JW (Contemporary Sociology-a Journal of Reviews, 1993)
Keywords: dept.eco; dept.fin